GE_GERICHTE C/18184/2014 vom 20. November 2015 - GE Cour de justice (2015)
MAINLEVÉE DÉFINITIVE; ACTE DE RECOURS; MOTIVATION; TITRE DE MAINLEVÉE; CONDITION SUSPENSIVE | CPC.321.1; CPC.326.1; LP.80.1; LP.81.1